Chaos during general election will not benefit country - Academicians - New Sabah Times English, (KK) (New Sabah Times English (KK), 2013)
KUALA LUMPUR: Any attempt to create chaos during the 13th general election will not be worthwhile and will not benefit the people, several academicians said yesterday. Universiti Utara Malaysia (UUM) School of Law, Government and International Studies lecturer Mohamad Faisol Keling, for instance, said no political party should resort to using such a tactic merely to grab power.